The Development of E-Handout Teaching Materials for the Sub-Concept of Structure and Function of Tissues in Plants - Anisa Rahmatina; Noorhidayati Noorhidayati; Aulia Ajizah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Learning in the 21st century is supported by mastery of technology. The utilization of technology in education can be implemented in the use of electronic teaching materials, one of which is E-Handout. The purpose of this study was to describe the needs analysis, validity and practicality of the results of the Development of E-Handout Teaching Materials for the Sub-Concept of Structure and Function of Tissues In Plants. This research is categorized as research and development (R&D) based on the 4D model. Data collection used teacher and students needs instruments, validity and practicality questionnaires. The research subjects were 3 experts and 12 students of class XI MIPA at SMA Negeri 1 Alalak. The results showed that first, the results of the needs analysis were